PERANCANGAN SISTEM APLIKASI REQUEST MAINTENANCE TEKNIK DI PERGURUAN TINGGI RAHARJA - Al Husain; Jaka Prima Maulana; Yuli Widiastuti (UNIVERSITAS RAHARJA, 2017)
The development of information technology is growing rapidly, making the system change and develop until the need for the desired information can be accessed easily and accurately. Likewise with the operational Higher Education Prog who want the reliability of a system. In the case of operational procurement needs and improvements in Higher Education Prog until now carried out by the technical staff directly working on demand through telvon or speak directly, so inadequate as a reminder of the task request repairs and procurement activity reports Staff. Itcreates the application of the procurement system maintenance activity reports technique realized with the use of paper media as the media filing staff. But the idea of the system method has the disadvantage that slows performance in making the report. From it does research bermetodekan data collection system is running, observation, interviews and analysis of the proposed system CSF, prototyping and testing methods as the establishment of the proposed system is adequate as the best alternative solution of the existing problems.